2002
DOI: 10.1007/s004050100406
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity studies on permethrin, DEET and diazinon in primary human nasal mucosal cells

Abstract: Possible genotoxic effects exerted by three widely used pesticides, permethrin, N,N-diethyl-m-toluamide (DEET) and diazinon, in primary human nasal mucosal cells were investigated. Primary nasal mucosa cells were prepared from tissue biopsies taken from 21 patients who underwent nasal surgery. Cells were exposed to 0.5-1.0 mM concentrations of permethrin, DEET and diazinon for 60 min. Genotoxic effects were detected by the alkaline microgel electrophoresis assay ("comet assay"). Within the concentration range,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 12 publications
4
42
1
4
Order By: Relevance
“…In another report, PM significantly increased the DNA damage in a concentration-dependent manner in healthy human lymphocytes (Undeger and Basaran 2005). Possible genotoxic effects in primary human nasal mucosal cells were also investigated by Tisch et al (2002). Their findings indicated a significant genotoxic response that was concentration dependent.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In another report, PM significantly increased the DNA damage in a concentration-dependent manner in healthy human lymphocytes (Undeger and Basaran 2005). Possible genotoxic effects in primary human nasal mucosal cells were also investigated by Tisch et al (2002). Their findings indicated a significant genotoxic response that was concentration dependent.…”
Section: Discussionmentioning
confidence: 94%
“…PM was shown to induce DNA damage on rat heart cells (Vadhana et al 2010). Furthermore, potential carcinogenicity of PM was ascertained in human nasal mucosal cells (Tisch et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise Undeğer and Başaran (2005) found that PM significantly increased DNA damage in human lymphocytes. Possible genotoxic effects in primary human nasal mucosal cells were also investigated by Tisch et al (2002). Their findings indicated a significant genotoxic response that was concentration dependent thereby they provided evidence for the potential carcinogenicity of PM to these cells.…”
Section: Discussionmentioning
confidence: 99%
“…PM was also shown to induce DNA damage on rat heart cells (Vadhana et al, 2010). Furthermore, potential carcinogenicity of PM was ascertained in human nasal mucosal cells (Tisch et al, 2002). In addition Hu et al (2010) demonstrated that PM induced oxidative stress in rat adrenal pheochromocytoma (PC12) cells.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian and nonmammalian bioassays and toxicology studies have confirmed its carcinogenic potential (8,9). PM exposure leads to DNA damage in humans and experimental animals (1,10,11). It induces oxidative damage to purine bases in the heart cells (12) and produces single-and double-strand breaks in striatum cells (13).…”
mentioning
confidence: 99%